2013
DOI: 10.1371/journal.pone.0064600
|View full text |Cite
|
Sign up to set email alerts
|

HDAC Up-Regulation in Early Colon Field Carcinogenesis Is Involved in Cell Tumorigenicity through Regulation of Chromatin Structure

Abstract: Normal cell function is dependent on the proper maintenance of chromatin structure. Regulation of chromatin structure is controlled by histone modifications that directly influence chromatin architecture and genome function. Specifically, the histone deacetylase (HDAC) family of proteins modulate chromatin compaction and are commonly dysregulated in many tumors, including colorectal cancer (CRC). However, the role of HDAC proteins in early colorectal carcinogenesis has not been previously reported. We found HD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
95
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 122 publications
(98 citation statements)
references
References 47 publications
3
95
0
Order By: Relevance
“…Mechanistically, this provides a general road map of which morphological structures to investigate. Ongoing research to implicate specific mucosal components suggests that the alterations occur due to a combination of intracellular (e.g., condensation of chromatin in the nucleus [2][3][4] or abnormalities in the cytoskeleton 5 ) and extracelluar components (e.g., collagen cross-linking 4,6 ). Interestingly, these changes appear to be attenuated versions of other classical markers of neoplasia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanistically, this provides a general road map of which morphological structures to investigate. Ongoing research to implicate specific mucosal components suggests that the alterations occur due to a combination of intracellular (e.g., condensation of chromatin in the nucleus [2][3][4] or abnormalities in the cytoskeleton 5 ) and extracelluar components (e.g., collagen cross-linking 4,6 ). Interestingly, these changes appear to be attenuated versions of other classical markers of neoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Although the concept of field carcinogenesis has been under study since 1953, the ultrastructural changes that compose the field are still being uncovered. Several changes whose role in field carcinogenesis has been implicated include chromatin condensation, [2][3][4] cytoskeleton disruption, 5 and collagen crosslinking in the extracellular matrix. 6 Still, the exact origin and carcinogenic advantage these transformations confer are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…This relation is derived from the properties of fractal media with conserved mass and volume-as compaction increases locally, the variations in mass density (heterogeneity) must also increase. Previous molecular dynamics simulations have further confirmed that increases in δn*L c correspond to an increase in macromolecular compaction, and experimental results have shown that this increase within the nucleus quantitatively describes an increase in chromatin heterogeneity (21,25,26).…”
Section: Resultsmentioning
confidence: 69%
“…Specifically, the HDAC families of proteins modulate chromatin compaction and are commonly deregulated in many tumors, including colorectal cancer (23). HDACIs interfere with tumorigenic HDAC activity; however, the precise mechanisms involved in this process remain to be elucidated (23).…”
Section: Discussionmentioning
confidence: 99%
“…HDACIs interfere with tumorigenic HDAC activity; however, the precise mechanisms involved in this process remain to be elucidated (23). The anti-proliferative effects of VPA on human colorectal cancer cells may be based on the direct inhibition of HDACs by a direct influence on enzymes that are responsible for acetyla- tion and deacetylation of nucleosomal histones.…”
Section: Discussionmentioning
confidence: 99%